Revisiting 12C16O+first negative system: An experimental and theoretical study. (November 2020) - Ventura, Laiz R.; da Silva, Ramon S.; Ballester, Maikel Y.; Fellows, Carlos E.
Highlights: In this article, the 12 C 16 O + First Negative system ( B 2 Σ + - X 2 Σ + ) is analyzed, both experimentally and theoretically. FTS in the ultraviolet region and ab initio multiconfiguration self-consistent field (MCSCF) method have been used. The study carried out in this work brings new values for the spectroscopic constants and potential energy curves. Thanks to this study, it was possible to correct discrepancies in some band origins with respect to recent previous work. Abstract: In this article, a new study of the 12 C 16 O + First Negative system (B 2 Σ + → X 2 Σ + ), is performed both theoretically and experimentally. From an experimental point of view, high-resolution Fourier transform spectroscopy in the ultraviolet region was used. On the theoretical side, ab initio electronic energies were calculated employing the state-averaged multiconfiguration self-consistent field (MCSCF) method, followed by the icMRCI/AV6Z level of theory with Davidson modification. Through these two analyses, theoretical and experimental, values for the spectroscopic constants, potential energy curves, and parameters concerning the transition are presented. The results, both theoretical and experimental, obtained in this work are compared with values obtained in previous works, pointing out certain discrepancies with more recent works and providing new and improved values for the band origins of this transition.